Antibodies To Insulin In Children With Diabetes Mellitus (Texas Journal of Medical Science, 2025)
The levels of antibodies to insulin analysed in 58 children with diabetes mellitus with the help of enzyme immunoassay were found to be increasing with the disease duration and insulin dependence in the patients. The concentration of antibodies was found correlating with the frequency of viral infections in the anamnestic data of the children, and with the presence of microangiopathic, lipodystrophic and immunopathologic conditions